External application of Traditional Chinese medicine in the treatment of acute gouty arthritis (中药外敷治疗急性痛风性关节炎临床效果及护理) - LI Juan (李娟); ZHENG Xiaoya (郑小雅); ZHANG Haiying (张海英); DU Danying (杜丹颖); HAN Shuhua (韩淑花); LI Yan (李雁) (Association of Integrative Nursing, 2023)
Objective To observe the clinical effect of external application of Traditional Chinese Medicine(TCM) in the treatment of acute gouty arthritis. Methods Totally 61 patients with acute gouty arthritis who met the inclusion criteria were included as research subjects. They were treated with TCM external application which designed to promote blood circulation and remove blood stasis within 2 hours after admission. The changes of Visual Analogue Scale of pain and TCM symptom score before and after treatment were observed. Results After treatment, VAS score and TCM symptom score of patients were significantly decreased, with a significant difference(P< 0. 05). Conclusion The external application of Traditional Chinese Medicine in the treatment of gouty arthritis has definite curative effect, simple operation and low price, which is worth promoting. (目的 观察中药外敷治疗急性痛风性关节炎的临床疗效。方法 选取符合纳入标准的61例急性痛风性关节炎患者为研究对象, 在入院2 h内采用自拟活血化瘀中药局部外敷, 观察其治疗前后疼痛视觉模拟评分(VAS)及中医症候积分的变化。结果 治疗后, 患者VAS评分及中医症候分均较治疗前降低, 差异有统计学意义(P＜0. 05)。结论 采用中药外敷治疗痛风性关节炎疗效确切, 且操作简单。)